DIGITAL LABOR SOLIDARITIES, COLLECTIVE FORMATIONS, AND RELATIONAL INFRASTRUCTURES - Soriano, Cheryll Ruth; Grohmann, Rafael; Chen, Yujie; Karatzogianni, Athina; Qiu, Jack; Cabanes, Jason Vincent; Alves, Paula; Dey, Andrija (AoIR Selected Papers of Internet Research, 2020)
Research on digital worker experiences have shed light on the problematic realities of digital labor, which include increasing levels of stress and anxiety over financial and career instability, physical exhaustion, and isolation - all of which underscore the precarity that belie the optimistic facade of labor under the new economy. Given the multiple constraints underlying collective formation among digital workers, this panel explores the characteristics and dynamics of emerging forms of collective organisation among digital workers by reflecting on experiences from China, the Philippines, Brazil, and India. Examining experiences of digital labor organisation and challenges to build solidarity across national and even regional experience, the panel hopes to enrich the discussion in terms of the politics, cultural nuances, and local meanings useful for examining digital worker expressions of resistance and solidarity amidst continuing technological development and platform reforms. This close examination of diverse forms of collective organisation, as well as the relational infrastructures underlying them, aims demonstrate how workers challenge the dominant claims of global capitalism while steep in recognition of the opportunities that these offer.